Efficacy of Sambiloto Extracts, Andrographis paniculate, (Burm. F) in Inhibiting Diabetic Retinopathy Progression: An in Vivo Study: Oral Presentation - Experimental Study - Resident - Shariff, Muhammad Apriliandy; Amin, Ramzi; Ansyori, AK. (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Diabetic retinopathy (DR) is one of diabetes mellitus complication and occurred in retinal microvascular. This study was aimed to investigate the efficacy of Sambiloto, Andrographis paniculate (A. paniculata) extract on glycemic profile, antioxidant and inflammatory cytokine parameters in diabetic rats, and phytochemical analysis of A. paniculata. Methods A. paniculata extract (APE) was carried out by maceration with ethanol. Diabetes mellitus in Wistar male rats was induced with streptozotocin. Retinal vessel diameters were estimated using a method by Vucetic. Inflammatory cytokine and antioxidant parameters were evaluated in retinal tissue. The alkaloid and flavonoid contents in extract were analyzed using thin layer chromatography method. Results Funduscopic examination presented some changes in the diameter of the blood vessels. The vessel diameter in the diabetic retinopathy group with APE in concentration of 100 and 200 mg/kg BW groups was significantly lower than in the DR group (p<0.05). The administration of APE in dosages of 100 and 200 mg/kg BW showed reduced glutathione, SOD, and catalase levels compared to the DR group (p<0.05). Conclusion A. paniculata extract doses of 100 and 200 mg/kg BW improved diabetic retinopathy in rats through hypoglycemic effects, antioxidant effects, and anti-inflammatory mechanisms.